2011
DOI: 10.1016/j.antiviral.2011.02.005
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 dual/mixed tropic isolates show different genetic and phenotypic characteristics and response to maraviroc in vitro

Abstract: Please cite this article in press as: Svicher, V., et al., HIV-1 dual/mixed tropic isolates show different genetic and phenotypic characteristics and response to maraviroc in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Phenotypic tropism determination Phenotypic tropism of recombinant viruses was evaluated by a multiple replication cycle assay on U87MG-CD4 + /CCR5 + / CXCR4 + -astroglioma-expressing cells [3,7].…”
Section: Production Of Recombinant Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenotypic tropism determination Phenotypic tropism of recombinant viruses was evaluated by a multiple replication cycle assay on U87MG-CD4 + /CCR5 + / CXCR4 + -astroglioma-expressing cells [3,7].…”
Section: Production Of Recombinant Virusesmentioning
confidence: 99%
“…Nevertheless, it has been suggested that maraviroc could also be used to improve therapy efficacy in subjects infected with dual/mixed tropic viruses [3,4,7,8]. The A4001029 study is a unique exploratory, randomized, double-blind, multicenter trial designed to assess the use of maraviroc in treatmentexperienced subjects infected with non-R5 viruses which has proved the efficacy of the regimen in 27% of subjects in the maraviroc twice-daily arm [8].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This case report demonstrates that dual-tropic viruses, capable of using both co-receptors in phenotypic assays, can be inhibited by maraviroc if they have a CCR5 co-receptor preference in vivo. 97 Svicher et al 98 conducted an in vitro study and their results indicated that in both pure-X4 and R5/X4(+)-isolates, extensive prevalence of X4-using species was observed. In vitro selectionexperiments with CCR5-inhibitor maraviroc showed no-emergence of X4-tropic variants for all R5-and R5(+)/X4-isolates tested.…”
Section: Recent Investigationsmentioning
confidence: 99%
“…However, despite the use of current antiretroviral drugs, HIV-1 can still persists in infected individuals by accumulating mutations, which make it resistant to one or more drugs. The antiretroviral drug resistant mutations can be identified by one or more of the following: (a) in vitro passage experiments or site directed mutagenesis studies (Clark et al, 2006); (b) mutagenically separated PCR (Frater et al, 2001); (c) drug susceptibility testing (Petropoulos et al, 2000;Svicher et al, 2011); (d) nucleotide sequencing of viruses from patients failing a specific drug (McNicholas et al, 2011;Shulman et al, 2004); (e) correlation studies between genotype at baseline and virologic response in patients exposed to a specific antiretroviral drug (Demeter et al, 2008). Currently, more than 200 mutations in the HIV-1 pol and env genes associated with resistance to current antiretroviral drugs, which include reverse transcriptase inhibitors (RTIs), protease inhibitors (PIs), integrase inhibitors (INI), fusion inhibitors and attachment inhibitors respectively, have been identified (V. A.…”
Section: Point Mutations and Hiv-1 Drug Resistancementioning
confidence: 99%